Teaching on the education frontier instructional strategies for online and blended classrooms, grades 5-12 - Kipp, Kristin 1980- (Jossey Bass teacher, 2013)
"A groundbreaking guide to facilitating online and blended coursesThis comprehensive resource offers teachers in grades K-12 a hands-on guide to the rapidly growing field of online and blended teaching. With clear examples and explanations, Kristin Kipp shows how to structure online and blended courses for student engagement, build relationships with online students, facilitate discussion boards, collaborate online, design online assessments, and much more. Shows how to create a successful online or blended classroom Illustrates the essential differences between face-to-face instruction and online teaching Foreword by Susan Patrick of the International Association for K-12 Online Learning This is an essential handbook for learning how to teach online and improve student achievement"--Provided by publisher.